TREND PENELITIAN TUGAS AKHIR MAHASISWA PENDIDIKAN KIMIA UNISKA MAB (2018-2021): KAJIAN PUBLIKASI ILMIAH - Antoni Pardede; Rr. Ariessanty Alicia Kusuma Wardhani; Viony Febriyanti; Rahmah Rahmah; M. Syahriza Finata; Miftahul Huda; Mardan Mardan; Elma Yulida; Chandra Halim (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Scientific publications are the estuary of research conducted by researchers and are becoming a wealth source of research information. The thesis published from 2018 to 2021 was reviewed to determine the trend of thesis research for the chemistry education department at Uniska MAB, using an analysis of the type, design, subject, object, processing, and analysis of the research data used. Based on the analysis, the trend of thesis research (2018 - 2021) was (1) 50% of quantitative research types, (2) 30% of the research design was non-equivalent control group design (quasi-experimental), (3) the selected research subjects were high school students/equivalent grade XI, (4) 30% of research data was collected through test questions, (5) the data analysis was explained by statistical techniques, (6) the chosen research object was to measure student learning outcomes. The six points have identified guidelines and references that have become research trends in the past 4 years in the chemistry education department at Uniska MAB and can be used to develop research themes for advanced research studies in chemistry education.